An embedded dynamic querying system - Ong, Chooi Sim (Faculty of Computer Science and Information Technology, 1995)
As information technology continues to grow rapidly, we need to incorporate simple querying features to allow end users to gain access to information. Often, the query power is just limited to the expert user group who are proficient in the use of SQL. However, "visual dynamic querying" is a promising approach that may deliver the required fast and easy interface for the use of non-computer experts.